STRATEGI KOMUNIKASI PEMASARAN TERPADU(INTEGRATED MARKETING COMMUNICATION (IMC)) YANG DITERAPKAN OLEH RE CAFFE PLATINUM PEKANBARU DALAM MENINGKATKAN PELANGGAN - Mustiar Hasri; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Initial open, Re Caffe Platinum visitors around 1560 visitors per year, this is due to the introduction of the new audience but with enough introductions it has made a good income for the early stage. As the process of introducing Re Caffe Platinum gets more visitors, after entering the next year the Cafe visitor reaches 1,752 visitors, much higher than the number of visitors the previous year. This is a success for Re Caffe Platinum. In the third year since the founding of Re Caffe Platinum there was a drop in visitor numbers of as many as 1,488 visitors. In 2014 the decline was due to the competition with similar cafes reaching 1,428 visitors.This research uses descriptive qualitative research method that is data collection technique done by observation, interview, and documentation. Sample intake for informants using purposive sampling technique. Using the data validity checking technique through extension of participation and triangulation. The subject of this study was 6 (six). Validation of data validity by extension of participation and triangulation.The result of this research shows that strategy of Re Caffe Platinum Pekanbaru in improving customer is using Integrated Marketing Communication (IMC) strategy. Integrated Marketing Communication Strategy (IMC) is Advertaising, Sales Promotion, public relations, sponsorship, Packaging, social media and web sites. The IMC strategy is able to contribute to the customer to remain loyal to Re CaffePlatinum. Meanwhile, Re Caffe Platinum Pekanbaru is facing an obstacle in implementing Integrated Marketing Communication (IMC) strategy.Keywords: integrated marketing communication strategy, customer